Phosphorus Mitigation to Control River Eutrophication: Murky Waters, Inconvenient Truths, and "Postnormal" Science. Issue 2 (1st March 2013) - Jarvie, Helen P.; Sharpley, Andrew N.; Withers, Paul J. A.; Scott, J. Thad; Haggard, Brian E.; Neal, Colin
Abstract : This commentary examines an "inconvenient truth" that phosphorus (P)‐based nutrient mitigation, long regarded as the key tool in eutrophication management, in many cases has not yet yielded the desired reductions in water quality and nuisance algal growth in rivers and their associated downstream ecosystems. We examine why the water quality and aquatic ecology have not recovered, in some case after two decades or more of reduced P inputs, including (i) legacies of past land‐use management, (ii) decoupling of algal growth responses to river P loading in eutrophically impaired rivers; and (iii) recovery trajectories, which may be nonlinear and characterized by thresholds and alternative stable states. It is possible that baselines have shifted and that some disturbed river environments may never return to predisturbance conditions or may require P reductions below those that originally triggered ecological degradation. We discuss the practical implications of setting P‐based nutrient criteria to protect and improve river water quality and ecology, drawing on a case study from the Red River Basin in the United States. We conclude that the challenges facing nutrient management and eutrophication control bear the hallmarks of "postnormal" science, where uncertainties are large, management intervention is urgently required, and decision stakes are high. We argue a case for a more holistic approach to eutrophication management that includes more sophisticated regime‐based nutrient criteria and considers other nutrient and pollutant controls and river restoration (e.g., physical habitat and functional food web interactions) to promote more resilient water quality and ecosystem functioning along the land–freshwater continuum.